System Approach to the Combined Use of Large Language Models and Classical Models in Foresight Tasks - Володимир Савастьянов; Михайло Столяр (KPI Science News)
Background. Large Language Models (LLMs) and their associated agents have spread wide technology and represent a significant advancement in recent times. These state-of-the-art models expose valuable potential, but they are not devoid of restrictions, inefficiencies, and limits. This article investigates the exploration of these constraints within specific domain areas and prediction problems as examples.